Implementation of Multicultural Learning as Effort to Build Technology-Based Tolerance Character Value in Elementary Schools - Muh. Asharif Suleman; Zulfi Idayanti; Basri (JIP Jurnal Ilmiah PGMI, 2024)
Multicultural learning has occupied a key position in modern education, serving as an important foundation for strengthening tolerance and deepening cross-cultural understanding among students. The aim of this research is to determine the application of multicultural learning as a step in cultivating technology-based values of tolerance. This research is quantitative. This research data was processed using the JASP (Jeffrey's Amazing Statistics Program) program. This research uses primary data, with a total of 60 respondents from schools in Indonesia. Various factors are considered to ensure a comprehensive understanding of the education systems across participating countries. The following are some of the main variants or criteria that are usually assessed for elementary schools consisting of 10 private schools and 50 public schools in the 2018 PISA sample: school resources, educational practices, learning environment, educational outcomes, and technology integration.The research results show that the technology variable T1 Number of digital devices shows significant positive results, T2 also has a significant impact on Teachers' pedagogical skills in integrating digital tools, and T3 Effective Online Learning Platform also shows significant results in improving multicultural learning. Meanwhile, the variable M1 Study the culture of various countries did not show significant results, but M2 M2: Study cultural differences had a significant positive effect, and M3 Organizing multicultural learning also had a significant positive effect on increasing multicultural learning because the probability value was below the significance value <0.05. The implications of this research can provide a deeper understanding of the role of multicultural learning in forming attitudes of tolerance, as well as the use of technology as a means to increase its effectiveness.